2011
DOI: 10.1128/aem.05285-11
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-Associated Bacteria Are Strictly Maintained in Two Closely Related but Geographically Distant Sponge Hosts

Abstract: The giant barrel sponges Xestospongia muta and Xestospongia testudinaria are ubiquitous in tropical reefs of the Atlantic and Pacific Oceans, respectively. They are key species in their respective environments and are hosts to diverse assemblages of bacteria. These two closely related sponges from different oceans provide a unique opportunity to examine the evolution of sponge-associated bacterial communities. Mitochondrial cytochrome oxidase subunit I gene sequences from X. muta and X. testudinaria showed lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
105
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 45 publications
17
105
1
1
Order By: Relevance
“…And AOB sequences retrieved from N. nodastrella in Cluster 3 group with sequences from Dysidea avara from the Mediterranean. Such diverse distribution of bacterial communities has also been reported in earlier studies, with geographically distant sponges showing similar sponge-associated Bacteria (Montalvo & Hill 2011, Yang et al 2011, Ribes et al 2012. Two of the wellsupported clusters (Clusters 1 and 2) contained mainly sequences from sponges and sediment, while Cluster 6 contained only sequences from sponges and water.…”
Section: Diversity Of Sponge-associated Aoa and Aobsupporting
confidence: 79%
“…And AOB sequences retrieved from N. nodastrella in Cluster 3 group with sequences from Dysidea avara from the Mediterranean. Such diverse distribution of bacterial communities has also been reported in earlier studies, with geographically distant sponges showing similar sponge-associated Bacteria (Montalvo & Hill 2011, Yang et al 2011, Ribes et al 2012. Two of the wellsupported clusters (Clusters 1 and 2) contained mainly sequences from sponges and sediment, while Cluster 6 contained only sequences from sponges and water.…”
Section: Diversity Of Sponge-associated Aoa and Aobsupporting
confidence: 79%
“…Additional and distinct patterns might be revealed on lower taxonomic levels given a more representative taxonomic sampling. It is noteworthy, however, that the HMA/LMA characteristics are conserved in closely related species over time and space when collected from different geographic regions (Wilkinson, 1978;Montalvo and Hill, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…studies (e.g., Littman et al, 2009;Pantos et al, 2015;Roder et al, 2015) have suggested that geographic location and environmental settings can determine the holobiont microbiome, whereas others (e.g., Hentschel et al, 2002;Fraune and Bosch, 2007;Montalvo and Hill, 2011;Lawler et al, 2016) have shown that bacterial communities are species-specific associations conserved over time and space. Moreover, coevolution of bacteria and coral has been proposed (Thompson et al, 2015), as it was demonstrated for Endozoicomonas symbionts in corals with contrasting life-history traits and across global scales (Bayer et al, 2013;Neave et al, 2016Neave et al, , 2017.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%